Integration of emotional intelligence and creativity in e-learning environment - Sukumaran, S.D.; Idris, A.R.; Varatharajoo, C.; Rengasamy, S.; Raju, S.; Sia Seng Lee, W.A. (2014)
This purpose of this study is to analyse the relationship of emotional intelligence and creativity on employees’ work performance and commitment.Increasing of technological transformation, competition and globalization continues perhaps with increasing employees’ work performance and commitment (Greven, 2008). According to Turner, Barling and Zacharatos (2012), at present employees have to be allied to their work physically, emotionally and mentally in order to deliver remarkable performance as educator. The critical issues are in private higher education institutions educators and managerial level of educators facing complexity, peculiarity and challenges of a transformation towards e-learning as to fulfill the Key Result Area that set by Ministry of Higher Education. Poor monitoring emotional intelligence and creativity may slow down the employees’ performance (MacCann & Roberts, 2008). As a result, employees are not motivated to work hard, besides that they do not have the ability to manage their emotions. Managers fail to give feedbacks and stimulate employees. Additionally, they were also facing difficulties in handling responsibility to change in order to enhance their educator’s work commitment and improve their performance.The results indicated that there is a positive relationship between emotional intelligence and educators work commitment (r=0.349, p<0.01). Educator can develop their emotional intelligence skills by being creative to expand their capability to think, to produce new ideas, to make changes in an organization which can influence their attitude at work and to increase their commitment through organization. This research fills the gap of literature and will contribute to academician and professional development organizers in empowering educators to support e-learning.